“Had its history been different, South Africa would probably have been one of the most visited places in the world.”? : analysing South African tourism history with special reference to the Western Cape, 1980-2000 - Carstens, Rouzanne (Stellenbosch : Stellenbosch University, 2022)
Thesis (MA)--Stellenbosch University, 2022.